Delusional disorder : paranoia and related illnesses - Munro, Alistair (Cambridge University Press, 1999)
Provides a comprehensive review of delusional disorder, a condition that was only reintroduced into modern psychiatric diagnosis in 1987. An invaluable reference for psychiatrists and other clinicians, this authoritative text is illustrated throughout with case histories and includes clear guidelines on diagnosis and treatment.